Modelling rainfall‐induced phosphorus loss with eroded clay and surface runoff - Chen, Minghong; Li, Yun; Wang, Chaozi; Walter, M. Todd; Huang, Lei (Hydrological processes, 2023)
Phosphorus (P) loss via runoff will reduce soil fertility and cause water eutrophication. Although P is lost as both particulate phosphorus (PP) and soluble phosphorus (SP), the existing P transport models for landscapes rarely consider PP and its exchange with surface runoff. We developed an integrated P transport model which coupled both SP and PP transport mechanisms based on the Rose–Gao model and assessed it via laboratory experiments. We also introduced a temporal varying P partition coefficient Kd into the model to reveal the impacts of rapid changes in the water environment on P adsorption and desorption. Experiments using kaolinite mixed soil and montmorillonite mixed soil were conducted under artificial rainfall events. The results show that the P transport model simulates the concentrations of eroded sediment, SP, and PP in surface runoff, with good agreement with the measured values (all R2 > 0.88). Kaolinite mixed soil had larger sediment and SP concentrations in the runoff than montmorillonite mixed soil. In addition, compared with the no Kd model (Gao model) and the constant Kd model, our model provided simulation results that most closely matched the experimental data. Considering the influence of eroded sediment and the P dynamic partitioning between sediment and water to the surface, the P transport model can provide an effective tool for P dynamics with water and sediment in surface runoff. An integrated phosphorus (P) transport model is developed based on the Rose–Gao model. A dynamic partition coefficient Kd is introduced into the P transport model. Soils mixed with kaolinite and montmorillonite were tested for model validation. The importance of eroded sediment on the P transport is presented and analysed.